2007
DOI: 10.1103/physrevb.75.024207
|View full text |Cite
|
Sign up to set email alerts
|

Resonant susceptibility of dielectric glasses in magnetic field

Abstract: The anomalous magnetic field dependence of dielectric properties of insulating glasses in the temperature interval 10mK < T < 50mK is considered. In this temperature range, the dielectric permittivity is defined by the resonant contribution of tunneling systems. The external magnetic field regulates nuclear spins of tunneling atoms. This regulation suppresses a nuclear quadrupole interaction of these spins with lattice and, thus, affects the dielectric response of tunneling systems. It is demonstrated that in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Elec-trical conduction in these glasses occurs by the hopping of electrons from Cu + to Cu 2+ . The study of dielectric properties over a wide range of frequencies and temperatures of the glass materials not only helps in accessing the insulating character and understanding the conduction phenomenon but to a large extent also gives information on the structural aspects of the glasses [27][28][29][30]. It has been observed that even in very small quantities, these metal ions (such as copper) dissolved inadvertently in the Na 2 O-P 2 O 5 -ZnO glass matrix make these glasses coloured leading to the strong influence on their dielectric properties and optical transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Elec-trical conduction in these glasses occurs by the hopping of electrons from Cu + to Cu 2+ . The study of dielectric properties over a wide range of frequencies and temperatures of the glass materials not only helps in accessing the insulating character and understanding the conduction phenomenon but to a large extent also gives information on the structural aspects of the glasses [27][28][29][30]. It has been observed that even in very small quantities, these metal ions (such as copper) dissolved inadvertently in the Na 2 O-P 2 O 5 -ZnO glass matrix make these glasses coloured leading to the strong influence on their dielectric properties and optical transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The study of dielectric properties, such as constant, loss and a.c. conductivity over a wide range of frequency and temperature not only help in assessing the insulating character of the glasses but also throw some light on the structural aspects of these glasses [17][18][19][20][21]. The current investigation is aimed at an understanding the influence of the titanium ions on structural aspects of PbO-Bi 2 O 3 -B 2 O 3 glasses by studying their dielectric and spectroscopic properties.…”
Section: Introductionmentioning
confidence: 99%